Analysis of the influence of branding on consumer perceptions of culinary products at “La Bugis” restaurant in Sidenreng Rappang Regency - Husnayani Husnayani; Muhammad Rusdi; Yayuk Astuti; Hartati Hartati (Edumaspul: Jurnal Pendidikan, 2025)
This study is motivated by the increasing competition in the culinary industry, which requires business actors to build strong branding in order to create positive consumer perceptions. The purpose of this research is to analyze the influence of branding on consumer perceptions of culinary products at La Bugis Restaurant in Sidenreng Rappang Regency and to identify the branding elements that contribute to customer loyalty. This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews with the owner, employees, customers, and the surrounding community, as well as through observation and documentation. Data analysis was carried out using data reduction, data display, conclusion drawing, and supported by NVivo 12 software for coding and visualization. The findings reveal that brand identity, the quality of traditional flavors, friendly service, comfortable atmosphere, and differentiation through local culture are the main factors in building positive consumer perceptions. In addition, word-of-mouth promotion and social media play an important role in strengthening brand image and customer loyalty. Thus, consistent branding based on customer experience has been proven to enhance the attractiveness and competitiveness of La Bugis Restaurant